Perkembangan Penulisan Tafsir Al-Qur’an di Indonesia Era Reformasi - Sofyan Saha (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
This paper examines the model of writing Quranic Exegesis (Tafsir) in Indonesia during reformation period. This aims to understand method (manhaj) and technique (uslub) in writing Quranic Exegesis from 2000s up to the present. It is found that there are three models of writing Quranic Exegesis during the era. Firstly, there is tafsir which only focuses on particular verses (ayat), chapter (surat) or parts (juz) of the Quran. Secondly, there is tafsirs which focuses on special themes (thematic) of the Quran. Thirdly, there are tafsirs which covers whole Quran (thirty Juz). It is also found that tafsir writing during reformation period continued interpretation paradigm of writing tafsir during 1990s. In term of writing technique, most tafsir written in reformation era are thematic. It is also found that there are collective writers and interdisciplinary study. Unfortunately, there are some tafsir written by scholar who does not qualify for writing tafsir (unqualified exsegesist).